Peningkatan Kemampuan Kosakata Bahasa Inggris Bagi Anak Usia Dini di Panti Asuhan Bumi Nusantara Medan - Misla Geubrina; H Hidayati; Hendra Mulia (LPPM STIKOM Tunas Bangsa, 2022)
English is an international language that everyone must understand to be a part of today's globalized world. This Community Service aims to improve English language skills for early childhood at the Bumi Nusantara Orphanage in Medan. The stages in this activity are (1) providing English language material which is done by introducing objects that are seen daily in early childhood at the Bumi Nusantara Orphanage in Medan, (2) accompanying the provision of English vocabulary to improve the English language skills, (3) Evaluating activities through criticism and suggestions on the usefulness and sustainability of activities. The output of this community service is being able to pronounce and produce the right intonation of spoken English orally.